"It's complicated" - talking about gout medicines in primary care consultations: a qualitative study. Issue 1 (December 2016) - Morris, Caroline; Macdonald, Lindsay; Stubbe, Maria; Dowell, Anthony
Abstract Background Gout is the most common form of inflammatory arthritis. It is associated with substantial co-morbidity and often managed in primary care. A greater understanding of the communication process between patients and healthcare professionals provides one way of improving the management of this condition. This paper describes communication about gout medicines and treatment between patients and primary care health professionals during routine consultations. Methods Video-recordings of 31 individual healthcare consultations between patients and a range of primary care practitioners (general practitioners, practice nurses, podiatrists, dietitians) from an archived database were reviewed. Consultations that encompassed any discussion about gout medicines and treatment were included (n  = 27) and were not solely restricted to those where gout was the presenting complaint. Themes were derived from an inductive qualitative analysis, from clinical and linguistic perspectives, based on the conversation between patients and practitioners about medicines and visual observation of these interactions. Results A number of factors were identified that had the potential to impact on the optimal management of gout in primary care. These included level of patient knowledge, patient attitudes to medicines, and the attributes of practitioner communication with patients. The latter related to the style of delivery and content of the information provided, and the ability of practitioners to make use of opportunities that arose to discuss these issues. Conclusions Patients with gout communicate at varying levels of complexity with a diverse range of primary care healthcare professionals about the treatment of their condition. It is important that all practitioners engaging with gout patients in this setting are knowledgeable about the current management of gout, provide clear, consistent and accurate messages, remain aware that these messages may need repeating over time, and are supportive of patients' medicine-taking preferences.